The nutritional, physico-chemical, and antioxidant changes during the production of soursop vinegar influenced by yeast and aeration - Mohd Zaini, Nurul Solehah; Na Ng, Ree; J. D. Abedelazeez, Khudair; Idris, Hamidah; Abd Rahim, Muhamad Hafiz (Universiti Putra Malaysia, 2024)
This study aims to produce soursop vinegar and evaluate how its nutritional composition changes during production. This process offers a solution to convert acidic fruits like soursop into a nutritious product with a longer shelf life. Fresh soursop juice was extracted using a mechanical press, followed by alcoholic and acetous fermentation under different aerobic and anaerobic conditions, with some samples aerated. The nutritional analysis included proximate composition, vitamin C content, acetic acid, pH, and soluble solids (TSS or ºBrix). Results during fermentation showed increased moisture content (90.73–93.99%) compared to the control (78.56%) and a decrease in protein content (0.5–0.61%) when Saccharomyces cerevisiae was present (1.53–1.84% without it). Acetic acid and vitamin C levels remained relatively stable, while ºBrix values significantly decreased (4.83–7.00 ºBrix) compared to the initial 15 ºBrix of the control during fermentation. Aeration during production improved the vinegar’s antioxidative capacity, with the highest enhancement observed when Acetobacter sp. was added. Overall, this study highlights the potential of soursop vinegar to retain the nutritional composition of the fruit, resulting in a healthier, natural product with an extended shelf life.